Non-Pharmacological Management of Osteoporosis Exercise, Nutrition, Fall and Fracture Prevention - Sinaki, Mehrsheed; Pfeifer, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This practical guide presents the most up-to-date information on the application of non-pharmacological and physical therapeutic measures, either used independently or in combination with pharmacotherapy, for the management of osteoporosis. Pharmacotherapy remains the primary treatment for osteoporosis, but to improve the biomechanical competence of bone and improve quality of life, there needs to be more comprehensive management approach involving non-pharmacological methods. The book opens with a discussion of the diagnosis, pathophysiology, complications and consequences of osteoporosis. Exercise, nutrition, orthotics, and other rehabilitation measures such as whole body vibration and electrical muscle stimulation, each described in details in chapters of their own, have had a beneficial impact on fall and fracture prevention as well as recovery post-fracture. In addition, the application of acupuncture for pain management and movement-based mind-body therapies like tai chi and the Feldenkrais method are explored. Providing a description of independent and adjuvant techniques and practices for treatment and improving quality of life, Non-Pharmacological Management of Osteoporosis is an excellent resource for endocrinologists, bone specialists, physical therapists, occupational therapists and all clinical practitioners and staff working with osteoporosis patients.
Burden, Risk Factors, and Prevention of Osteoporosis -- Physiology and Pathophysiology of Bone and Muscle -- Challenging Complications Related to Reduction of Biomechanical Competence of the Axial Skeleton -- Consequences of Bone Loss and Sarcopenia -- Role of Nutrition in Musculoskeletal Health -- Rehabilitation after Vertebral Fracture -- Exercise for Patients with Established Osteoporosis -- Exercise for the Prevention of Bone Loss -- Exercise for Treatment Post-Fracture -- The Role of Orthotics in Osteoporosis -- Whole Body Vibration: Physiology and Effect on Muscle and Bone -- Application of Electrical Modalities on Muscle Stimulation -- Kyphoplasty and Vertebroplasty: Benefits and Side-Affects -- Gait Aids for Prevention and Management of Falls -- Risk of Falls and Preventive Strategies -- Rehabilitation after Hip Fracture -- Pain Management and Quality of Life -- Recreational Exercises and Osteoporosis: Relaxation Techniques, Yoga and Tai Chi.
Keywords: Medicine; Endocrinology; Orthopedics; Medicine & Public Health; Endocrinology; Orthopedics